2008
DOI: 10.1007/s11606-008-0735-5
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Yoga Users: Results of a National Survey

Abstract: BACKGROUND: There are limited data on the characteristics of yoga users in the U.S. OBJECTIVE:To characterize yoga users, medical reasons for use, perceptions of helpfulness, and disclosure of use to medical professionals. METHODS:Utilizing cross-sectional survey data from the 2002 National Health Interview Survey (NHIS) Alternative Medicine Supplement (n=31044), we examined correlates of yoga use for health. The estimated prevalence from 2002 NHIS of yoga for health was 5.1% corresponding to over 10 million a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
240
5
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 294 publications
(281 citation statements)
references
References 45 publications
32
240
5
4
Order By: Relevance
“…About 14 million adult Americans (6.1% of the population) reported that yoga had been recommended to them by a physician or therapist (Macy, 2008). Indeed, about 80% of American yoga practitioners (more than 16 million people) reported that they had started practice explicitly to improve their health (Birdee et al, 2008;Clarke et al, 2002;Cramer et al, 2015a); and weight control is among the most frequently stated reasons for starting to practice (Park et al, 2014). While there is evidence to suggest that yoga is effective in promoting weight loss and improving body composition (Rioux and Ritenbaugh, 2013), no systematic review and/or metaanalysis on yoga for weight-related outcomes is available to date.…”
Section: Introductionmentioning
confidence: 99%
“…About 14 million adult Americans (6.1% of the population) reported that yoga had been recommended to them by a physician or therapist (Macy, 2008). Indeed, about 80% of American yoga practitioners (more than 16 million people) reported that they had started practice explicitly to improve their health (Birdee et al, 2008;Clarke et al, 2002;Cramer et al, 2015a); and weight control is among the most frequently stated reasons for starting to practice (Park et al, 2014). While there is evidence to suggest that yoga is effective in promoting weight loss and improving body composition (Rioux and Ritenbaugh, 2013), no systematic review and/or metaanalysis on yoga for weight-related outcomes is available to date.…”
Section: Introductionmentioning
confidence: 99%
“…This discomfort was multifaceted. Quite often, community yoga classes are largely made up of women who have experience with yoga, are familiar with the postures, and are physically fit [19]. Indeed, both of the men who expressed preferences about attending classes with women only attended one yoga class, and this happened despite one man stating that he liked attending classes with women.…”
Section: Discussionmentioning
confidence: 99%
“…That pilot trial demonstrated a large effect size for smoking cessation for the group that received the yoga intervention (odds ratio=4.56) [18]. While yoga's growing popularity among women in the USA has been documented [19,20], we were unable to identify any research showing trends for men's yoga practice in the USA. It is likely, however, that there are more men practicing yoga than is believed, given the growing popularity of yoga in general [19,20].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations